The implementation of optimized neural network to improve the accuracy of flow measurement by ultrasonic flowmeter - Parfeniuk, Oleksandr Ihorovich; Naumchuk, Oleksandr Mykolaiovych; Poliukhovych, Olena Olehivna; Mazurek, Pawel (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
It is proposed the technology of intellectual measurement of expenses with the use of an artificial neural network for overcoming the constraints caused by nonlinear characteristics of ultrasonic flowmeters. It is presented structural scheme of the proposed technology and structure of the model of the neural network